Molecular dynamics simulations of grain interactions in shock-compressed highly textured columnar nanocrystals - Heighway, P; McGonegle, F; Park, N; Higginbotham, A; Wark, J (American Physical Society, 2019)
While experimental and computational studies abound demonstrating the diverse range of phenomena caused by grain interactions under quasistatic loading conditions, far less attention has been given to these interactions under the comparatively dramatic conditions of shock compression. The consideration of grain interactions is essential within the context of contemporary shock-compression experiments that exploit the distinctive x-ray diffraction patterns of highly textured (and therefore strongly anisotropic) targets in order to interrogate local structural evolution. We present here a study of grain interaction effects in shock-compressed, body-centered cubic tantalum nanocrystals characterized by a columnar geometry and a strong fiber texture using large-scale molecular dynamics simulations. Our study reveals that contiguous grains deform cooperatively in directions perpendicular to the shock, driven by the gigapascal-scale stress gradients induced over their boundaries by the uniaxial compression, and in so doing are able to reach a state of reduced transverse shear stress. We compare the extent of this relaxation for two different columnar geometries (distinguished by their square or hexagonal cross-sections), and quantify the attendant change in the transverse elastic strains. We further show that cooperative deformation is able to replace ordinary plastic deformation mechanisms at lower shock pressures, and, under certain conditions, activate new mechanisms at higher pressures.